Pertumbuhan Pembangunan Real Estate Terhadap Perkembangan Urban Sprawl Di Kecamatan Tembalang - Shofarini, Dian Indah; Asnawi, Asnawi (Jurnal Tata Kota dan Daerah, 2014)
Urban sprawl is driven by population growth and need of land. Setioko (2009) and REI of Central Java (2012) says that urban development of Semarang City is sprawling through south and east of Semarang. Tembalang is one distric in Semarang who had the highest landuse changing which many center of activities with positive and negative effect. The aim of this research is to find out how real estate development growth influence the urban sprawl development in Tembalang. The approach of this research using a mixed method with housing growth analysis, housing market analysis, city-shape analysis and urban sprawl analysis. Real estate development for last 5 years affect the development of urban sprawl in Tembalang based on real estate development and people accessibility. Over the last 5 years, real estate development had contributed 0.34% to cover the backlog as many as 29% of the 26,131 houses until 2019. Housing and settlement planning need a grand design to accommodate the synchronization among urban planning, transportation and housing development Â in Semarang in order to minimize the sporadic and disorganized development. Keywords: real estate development, urban sprawl